Electrochemical Fingerprint Analyses Using Voltammetry and Liquid Chromatography Coupled with Multivariate Analyses for the Discrimination of Schisandra Fruits - Koichi Machida; Akira Kotani; Tomoya Osaki; Ayaka Kobayashi; Kazuhiro Yamamoto; Hideki Hakamata (Molecules)
The appearances of Schisandrae Sphenantherae Fructus (SSF) and Schisandrae Chinensis Fructus (SCF) are very similar. Thus, being able to distinguish between SSF and SCF is useful for the quality control of these herbal medicines. In this study, two kinds of electrochemical fingerprint analyses using voltammetry or HPLC with electrochemical detection (HPLC-ECD) were developed in combination with multivariate analysis for discriminating between SSF and SCF. The data sets of the oxidation current values from voltammograms of SSF and SCF samples ranging from +0.5 to +1.0 V were applied to perform a partial least squares discriminant analysis (PLS-DA). Moreover, the data sets of the current heights of the characteristic target peaks on the chromatograms at an applied potential of +0.9 V were also applied to perform PLS-DA. In each PLS-DA obtained from the voltammograms and chromatograms, the scores for the SSF samples were plotted on a different region compared with the scores for the SCF samples. Considering the results of the cross-validation, the HPLC-ECD clearly discriminated between the SSF and SCF samples when compared with the voltammetry. In conclusion, our results show that the present electrochemical fingerprint analyses coupled with PLS-DA are useful as a means for discriminating between the SSF and SCF samples.